The Role of Urban Forests as Carbon Sink: A Case Study in the Urban Forest of Banda Aceh, Indonesia - Ali Muhammad Muslih; Asyrafun Nisa; Sugianto; Tuti Arlita; Subhan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Forests have a role as carbon sinks and come under the spotlight when the world is facing the climate change problem. Urban forests have functions as the most effective carbon sinks. Banda Aceh City only has 7.15 ha of urban forest, and the vegetation that grows in the urban forest is essential for carbon emissions reduction. This study aimed to determine the potential tree biomass and carbon sink value in the BNI Urban Forest, Banda Aceh City, Indonesia. This study used vegetation analysis by inventory method with the census sampling method. The diameter of all trees was measured, and tree biomass, carbon stocks, and carbon sequestration were calculated. This study identified 16 tree species in the BNI Urban Forest with a total of 318 individuals, showing Casuarina equisetifolia as the most dominant tree (163 trees). The above-ground biomass, carbon stock, and carbon sequestration by the vegetation in the BNI Urban Forest were 24.66 tons/ha, 11.59 tons/ha, and 42.51 tons/ha, respectively. This study presented the vegetation conditions and the potential of carbon sequestration, which can be used to monitor and evaluate the benefits of the existence of urban forests in Banda Aceh. Keywords: carbon sequestration, carbon stock, green open space, tree biomass, urban forest